Gaya Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pada Sekolah Dasar - Hanafiah, Hanafiah; Berliana, Berliana; Margono, Margono (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to analyze the influence of the principal's leadership style on teacher performance in schools. The principal's leadership style is an important factor in creating a productive work environment and motivating teachers to achieve optimal results in the learning process. This study uses a quantitative approach using a questionnaire distributed to teachers in several schools. The respondents involved in this study were 9 teachers. The collected data were analyzed using linear regression techniques to test the relationship between principals' leadership style and teachers' performance. The results showed that there is a significant influence between the principal's leadership style and teacher performance. Democratic, and instructive leadership styles have a significant positive impact on teacher performance. Principals who apply a democratic leadership style provide opportunities for teachers to participate in decision-making and involve them in lesson planning. While instructive leadership.